ANALISIS EVAKUASI BENCANA TSUNAMI DENGAN METODE AGENT BASED MODELING STUDI KASUS GEDUNG PUSAT KEGIATAN MAHASISWA UNIVERSITAS BENGKULU - Saputra, Ramadhani Niko; Hardiansyah, Hardiansyah; Mase, Lindung Zalbuin (Inersia: Jurnal Teknik Sipil, 2019)
This study is designed to model the tendency of Gedung PKM users, Universitas Bengkulu using Agent Based Modelling Method. The vehicle survey is performed to obtain the peak-time period of parked vehicles in Gedung PKM. The questionnaire collecting is performed to obtain the information, which are later used to volume capacity ratio, volume, and road capacity. In this study, several road segments and alternative routes are observed during the evacuation. To inspect the suitability between the modelling and the observation, the simple linear regression analysis is performed. The results show that the most selected route is the shortest route with the best accessibility to reach the gateway, during the evacuation. The road saturation degree shows that there is a need to improve the local road performance in Universitas Bengkulu to ensure a faster evacuation process during tsunami.